Evaluation of serum-free culture conditions for primary human nasal epithelial cells - Mattinger, Cathrine; Nguyen, Trang; Schäfer, Dirk; Hörmann, Karl (International journal of hygiene and environmental health, 2002)
Defined culture conditions are essential for the interpretation of effects caused by volatile substances on human nasal epithelial cells (HUNEC) cultured in vitro. Conventionally, serum-containing media are used. However, the results of these experiments are of restricted value as serum contains many unknown and undefined substances. Not all serum-free media on the market are suitable for culturing primary HUNEC. Therefore, serum-free defined cell culture media were compared to evaluate optimal conditions for HUNEC and their cell lines. HUNEC were generated by trypsin digestion of mucosal tissue of the inferior turbinate. Cells were cultured on uncoated polystyrene dishes adding pre-warmed medium. Viability was controlled by trypan blue dye exclusion; colony forming units and cell morphology were controlled microscopically. The expression of different cytokeratins was studied immunocytochemically. Dulbecco's modified Eagle's medium was not suitable to grow HUNEC and passage them. HUNEC cultured in bronchial epithelial growth medium presented a more homogeneous cell morphology compared to other media and had a doubling time of 1.2 days. The maximum number of cell passages was 11 with bronchial epithelial growth medium.